Synergistic Use of Pyridine and Selenophene in a Diketopyrrolopyrrole‐Based Conjugated Polymer Enhances the Electron Mobility in Organic Transistors. (23rd June 2020) - Liu, Qian; Kumagai, Shohei; Manzhos, Sergei; Chen, Yingqian; Angunawela, Indunil; Nahid, Masrur Morshed; Feron, Krishna; Bottle, Steven E.; Bell, John; Ade, Harald; Takeya, Jun; Sonar, Prashant
Abstract: To achieve semiconducting materials with high electron mobility in organic field‐effect transistors (OFETs), low‐lying energy levels (the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO)) and favorable molecular packing and ordering are two crucial factors. Here, it is reported that the incorporation of pyridine and selenophene into the backbone of a diketopyrrolopyrrole (DPP)‐based copolymer produces a high‐electron‐mobility semiconductor, PDPPy‐Se. Compared with analogous polymers based on other DPP derivatives and selenophene, PDPPy‐Se features a lower LUMO that can decrease the electron transfer barrier for more effective electron injection, and simultaneously a lower HOMO that, however, can increase the hole transfer barrier to suppress the hole injection. Combined with thermal annealing at 240 °C for thin film morphology optimization to achieve large‐scale crystallite domains with tight molecular packing for effective charge transport along the conducting channel, OFET devices fabricated with PDPPy‐Se exhibit an n‐type‐dominant performance with an electron mobility (μe ) as high as 2.22 cm 2 V −1 s −1 and a hole/electron mobility ratio (μh /μe ) of 0.26. Overall, this study demonstrates a simple yet effective approach to boost the electron mobility in organic transistors by synergistic use of pyridine and selenophene in the backbone of a DPP‐based copolymer. Abstract : The synergistic use of pyridine and selenophene in a diketopyrrolopyrrole‐based copolymer helps obtain low frontier orbital energy levels, resulting in increased hole injection barrier and decreased electron injection barrier. Combined with favorable charge carrier transport in the polymer film, an n‐type‐dominant property in organic field‐effect transistors with a high electron mobility of 2.22 cm 2 V −1 s −1 is achieved.